CHARACTERISTICS OF EFFECTIVE JUNIOR HIGH SCHOOL ENGLISH TEACHERS IN KABUPATEN PACITAN BASED ON STUDENTS’ AND TEACHERS’ PERCEPTIONS - Diska Fatima Virgiyanti; Utami Widiati; Suharmanto Suharmanto (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2016)
This survey study wasdan guru intended  to investigate the characteristics of effective English teachers in Kabupaten Pacitan based on students’ and teachers’ perceptions. The study involved  108 students and 12 teachers who were randomly selected from the available data from Education Office of  Kabupaten Pacitan, East Java. The data were collected using students’ questionnaire and  teacher-self assessment covering 37 items and interview guide asking about students’ and teachers’ perceptions about characteristics of effective Junior High School English teachers in Kabupaten Pacitan. The findings show that  students and  teachers have different perceptions on the characteristics of effective English teachers.Penelitian survey ini bertujuan untuk mengetahui karakteristik dari guru Bahasa Inggris yang efektif di Kabupaten Pacitan berdasarkan persepsi guru dan siswa. Penelitian ini melibatkan 108 siswa dan 12 guru yang dipilih secara acak dari data yang diperoleh di kantor Dinas Pendidikan Kabupaten Pacitan, Jawa Timur. Pengumpulan data menggunakan kuesioner siswa dan penilaian individu guru yang mencakup 37 soal dan panduan wawancara yang menanyakan tentang persepsi siswa6 dan guru tentang karakteristik dari guru Bahasa Inggris SMP yang efektif di Kabupaten Pacitan. Hasil temuan menunjukkan bahwa siswa dan guru mempunyai persepsi yang berbeda terhadap karakteristik dari guru Inggris yang efektif.